Edmund Husserl’s Concept of Passivity - Osswald, Andrés Miguel (2014)
The change from static to genetic perspective involves an enlargement of the phenomenological field. The main subject is not anymore the description of the essential notes of a phenomenon but rather the search for its origins. New levels of objects and consciousness arise as consequence of this new approach. The structures of subjectivity revealed by the genetic inquiry constitute the field of passivity.